Quirks of subject (non-)extraction in Igbo. Issue 1 (24th June 2019) - Amaechi, Mary; Georgi, Doreen
Abstract : In this paper we present new data on a subject/non-subject extraction asymmetry in Igbo constituent questions. We provide evidence that the superficially morphological phenomenon reflects a deeper syntactic asymmetry: Unlike wh-non-subjects, wh-subjects cannot undergo local Ā-movement to the left periphery (SpecFOC ); rather, they have to stay in their canonical position SpecT. The same constraint also leads to the that -trace effect (absence of the complementizer) in the embedded clause of long subject wh-movement. We argue that what is responsible for the special status of wh-subjects is their high structural position. We provide an optimality-theoretic analysis of the asymmetry that is based on anti-locality: Local subject Ā-movement is excluded because it is too short. Moreover, we address the nature of apparent wh-in-situ in Igbo.